REKONSTRUKSI SUDU PRIMARY AIR FAN PLTU MENGGUNAKAN STANDAR NACA - Brilliant Dwinata (STKIP PGRI Situbondo, 2022)
This PA Fan is one of the vital components in the generating system that functions to drain air and carry fuel (coal) from the pulverizer to the boiler burner. The research has a focus on designing methods to reconstruct the blades in order to increase independence to maintain the reliability of turbo engine equipment. Damage to axial turbo engine equipment generally occurs as a defect in the blades. The method of self-constructing blades needs to be carried out to increase the speed of the repair process. The limitation in this study is that the blade airfoil profile is adjusted to the standards of the National Advisory Committee for Aeronautics (NACA). The benefit of the PA Fan blade reconstruction process is to find the technology of the PA Fan blade product and the basic concepts of the product design process as desired by the initial maker (design intent). The research methods used include: Measurement and geometric modeling of the PA Fan blade using the Mitutoyo Cyrsta-Apex S9106 Coordinate Measuring Machine which is connected to a non-contact laser scanner Mitutoyo Surface Measure 606 to obtain a collection of many coordinates of the measurement results (point clouds), then process point clouds processing to obtain a 3D model of the measurement results, after that identify the airfoil with the NACA standard, and the final stage is to process machine drawings of complete components with geometry specifications.